Entrepreneurship Promotion in Higher Education Institutions - Sousa, Áurea (2017)
The importance of entrepreneurship promotion has increased significantly in today's society, especially during periods of crises. This work is based on the responses obtained through a survey conducted on a sample of 305 undergraduates of the University of the Azores, enrolled in different science programs. The aim is to deepen the knowledge of the entrepreneurial propensity of higher education students in the Azores, and in that way the university can stimulate their interest in creating businesses. The main results obtained, using exploratory data analysis (from the univariate to the multivariate), are presented and discussed.